International agile teams in digital and virtual environment - Liška, Radek; Brunet-Thornton, Richard; Bureš, Vladimír; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2017)
The thesis discusses research on a selected international team that incorporates agile methodology framework. The team is distributed among multiple European states and has off-shore members in India. The research questions include cross-cultural aspects of teamwork, organizational viewpoint as well as other key areas of team cooperation. Analysis is performed based on questionnaire distribution and a series of structured interviews with members of the researched team. Research findings include a list of recommended changes to team organization and evaluation of cross-cultural and factors of cooperation and their impact. Research has provided an action plan and a set of research observations that include deep analysis of teamwork, the area has proven to be attractive for further research, hence the thesis is concluded with suggestions in this area.
Vedoucí práce: Richard Brunet-Thornton
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor dipl. práce]; diplomové práce; master's theses